PENGARUH PENGGUNAAN PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS TEKS BIOGRAFI - Aprilia, Lara; Gani, Erizal; Tressyalina, Tressyalina (Universitas Negeri Padang, 2018)
ABSTRACTÂ The research is aimed (1) to describe the skills of writing biography text of class X students of SMA Negeri 12 Padang before using cooperative type TSTS aided in audiovisual media, (2) to describe skill of writing biography text of class X students of SMA Negeri 12 Padang after using cooperative learning type TSTS Audiovisual media aids, (3) describe the influence of the use of cooperative audiovisual-type TSTS type cooperative learning on the writing skills of biographical text of grade X SMA Negeri 12 Padang students. The type of this research is quantitative research with experimental method. Based on data analysis, the use of cooperative type learning TSTS audiovisual media aids influence on writing skill biography of class X students of SMA Negeri 12 Padang.Â Kata kunci: pengaruh, pembelajaran kooperatif tipe TSTS, media audiovisual, menulis teks biografi